Gastrointestinal parasite prevalence in equids from the municipality of Oiba (Santander) - Bedoya Ríos, Miguel Ángel; Arcila Quiceno, Victor Hernán; Díaz Arias, Diego Andrés; Reyes Plata, Elkin Alfonso (Spei Domus, 2011)
The common use of equids for work and sports around the world makes the adequate care of these animals necessary. Endogenous and exogenous parasite infestations have been reported as a mayor cause of economical and performance losses as they affect the health of these animals. This research project, undertaken by the Universidad Cooperativa de Colombia, Bucaramanga branch, identified and characterized the gastrointestinal parasites of equids in the municipality of Oiba, Santander —1,420 meters above the sea level, 20 °C, located in the Cordillera Oriental (western mountain range of Colombia)— and defined the recommendations for therapeutic response with the adequate active principle. For this, we chose a population of two hundred equids from different areas of the town, from which fecal samples were taken (200 g approximately) and subsequently analyzed with a coprologic exam following the MacMaster technique. The sampled equids were distributed like this: 66% (132) horses, 26% (52) mules and 8% (16) donkeys. There was a 57% (114) of males and 43% (86) of females. Of the sampled equids, 92% presented gastrointestinal parasites, we detected a relatively high prevalence of the Trichostrongylus genre (90%, 182 cases). Trichonema and Strongylus parasites were uncommon.